HIV‐associated psoriasis: Epidemiology, pathogenesis, and management. Issue 2 (6th January 2019) - Ceccarelli, Manuela; Venanzi Rullo, Emmanuele; Vaccaro, Mario; Facciolà, Alessio; d'Aleo, Francesco; Paolucci, Ivana Antonella; Cannavò, Serafinella Patrizia; Cacopardo, Bruno; Pinzone, Marilia Rita; Pellicanò, Giovanni Francesco; Condorelli, Fabrizio; Nunnari, Giuseppe; et al.
Abstract: People living with HIV (PLWH) are affected by a higher incidence skin disorders, which are often associated with high morbidity and mortality. In particular, psoriasis affects PLWH severely and for a longer time than the general population. Human immunodeficiency virus (HIV) infection is characterized by a progressive decrease in CD4 + T‐cell count, and it could seem paradoxical that psoriasis exacerbations are more frequent in this subset of patients than the general population, even though it is commonly observed at any stage of infection. For a long time, there have been limited therapeutic choices for PLWH affected by psoriasis. The introduction of the combined antiretroviral therapy dramatically changed the natural course of both HIV and psoriasis in PLWH, leading to an improvement of quality and duration of life. However, the clinical severity of psoriasis in PLWH often requires the use of immunosuppressant drugs. Knowledge about their safety and efficacy are limited to case‐reports, small case‐series and studies, therefore their use has not yet entered the routine. Further studies are needed to determine if immunosuppressive drugs can be safely and effectively used in PLWH affected by psoriasis and other autoimmune disorders.